2020
DOI: 10.1590/0100-3984.2019.0054
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of magnetic resonance imaging for diagnosing hallux valgus

Abstract: Objective: To assess the accuracy of magnetic resonance imaging (MRI) for the diagnosis of hallux valgus using radiography during weight bearing as the gold standard. Materials and Methods: This was a retrospective analysis of all patients undergoing MRI of the foot and radiography of the foot during weight bearing at our institution between January and June of 2015. The hallux valgus angle (HVA) was measured on MRI and radiography. The Wilcoxon signed-rank test and simple linear regression were used in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The evaluation of the musculoskeletal system by magnetic resonance imaging (MRI) has been the subject of a series of recent publications in the radiology literature of Brazil (4)(5)(6)(7)(8) . Although MRI is not considered the gold standard for the evaluation of hallux valgus, because MRI scans are not acquired during weight bearing, we agree with Helito et al (9) that MRI could be used for the diagnosis of this condition, given its high prevalence and the frequent unavailability of radiographic studies during weight bearing, as stated in their study published in the previous issue of Radiologia Brasileira. Although the angles have been widely described on radiographs, the MRI measurements of hallux valgus have not been so assessed.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The evaluation of the musculoskeletal system by magnetic resonance imaging (MRI) has been the subject of a series of recent publications in the radiology literature of Brazil (4)(5)(6)(7)(8) . Although MRI is not considered the gold standard for the evaluation of hallux valgus, because MRI scans are not acquired during weight bearing, we agree with Helito et al (9) that MRI could be used for the diagnosis of this condition, given its high prevalence and the frequent unavailability of radiographic studies during weight bearing, as stated in their study published in the previous issue of Radiologia Brasileira. Although the angles have been widely described on radiographs, the MRI measurements of hallux valgus have not been so assessed.…”
supporting
confidence: 82%
“…The data presented by Helito et al (9) support the findings of Heineman et al (1) who demonstrated excellent interobserver agreement for the HVA and for the IMA on radiographs obtained during weight bearing and on MRI. Over the range of values that they tested, MRI was considered a viable imaging modality for diagnosing and assessing the severity of hallux valgus.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…A number of recent studies conducted in Brazil have highlighted the important role that imaging methods play in the evaluation of the musculoskeletal system (36)(37)(38)(39)(40) . In our study, the prevalence of imaging alterations in the CPN was high (36.8-39.4%), and the levels of interobserver and intraobserver agreement for these abnormalities were excellent (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies conducted in Brazil have highlighted the importance of using imaging methods for evaluating the musculoskeletal system ( 27 - 31 ) . The anatomy of the glenohumeral ligaments is complex and variable, various patterns having been described in the literature, which makes it difficult to gain a proper understanding of it.…”
Section: Discussionmentioning
confidence: 99%